PENGUJIAN KEAMANAN DENGAN METODE PENETRATION TESTING EXECUTION STANDARD (PTES) UNTUK MENEMUKAN KERENTANAN MISCONFIGURATIONS PADA PERANGKAT JARINGAN - Listartha, I Made Edy; Saskara, Gede Arna Jude (Electro Luceat, 2024)
This study examines the security of the WiFi network at Universitas Pendidikan Ganesha using the Penetration Testing Execution Standard (PTES) method. The aim is to identify and analyze vulnerabilities caused by misconfigurations within the university's WiFi infrastructure. The PTES method is employed to conduct testing through phases including pre-engagement interactions, intelligence gathering, threat modeling, vulnerability analysis, exploitation, post-exploitation, and reporting. The testing results reveal several key vulnerabilities related to improper configurations, such as the use of vulnerable protocols and insecure settings. Further analysis exposes potential risks that could be exploited by unauthorized parties to access sensitive data or disrupt services. The study provides recommendations for configuration improvements and mitigation steps to enhance WiFi network security at the university. The findings are expected to serve as a foundation for developing more effective security policies and better protection for network infrastructure in academic environments.